Similibus simile cognoscitur. O pensamento analógico medieval - Hilário Franco Júnior (Medievalista)
Although insufficiently considered by historiography, the analogical thought was the prevalent intellectual instrument in all sociocultural categories in medieval Europe. It was decisive for many forms of relation between the human ones and of those with nature. Taking into account this kind of reasoning based on homologies, symmetries, contiguities, correspondences and oppositions it is possible understand various aspects of knowledge, behaviors and emotions of medieval man. This is exemplified in the present article by the frequent use that the Middle Age made of analogies in mathematics, cartography, medicine, theology, biblical exegesis, liturgy, etymology, and literature, among other fields of human activity.